
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


2,\(pt\Leftrightarrow12\left(\sqrt{x+1}-2\right)+x^2+x-12=0\)
\(\Leftrightarrow12\cdot\frac{x-3}{\sqrt{x+1}+2}+\left(x-3\right)\left(x+4\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(\frac{12}{\sqrt{x+1}+2}+x+4\right)=0\)
Vì \(\left(\frac{12}{\sqrt{x+1}+2}+x+4\right)\ge0\left(\forall x>-1\right)\)
\(\Rightarrow x=3\)

Bài 1:
\(A=\sqrt{\frac{a+\sqrt{a^2-b}}{2}}+\sqrt{\frac{a-\sqrt{a^2-b}}{2}}=B+C\)
\(B=\sqrt{\frac{\left(a+\sqrt{b}\right)+2\sqrt{\left(a-\sqrt{b}\right)\left(a+\sqrt{b}\right)}+\left(a-\sqrt{b}\right)}{4}}=\frac{1}{2}.\sqrt{\left[\sqrt{\left(a+\sqrt{b}\right)}+\sqrt{\left(a-\sqrt{b}\right)}\right]^2}\)
\(B=\frac{1}{2}\left[\sqrt{a+\sqrt{b}}+\sqrt{a-\sqrt{b}}\right]\)(1)
\(C=\sqrt{\frac{a-\sqrt{a^2-b}}{2}}=\frac{1}{2}.!\left[\sqrt{a+\sqrt{b}}-\sqrt{a-\sqrt{b}}\right]!\) do \(a\ge\sqrt{b}\ge0\) \(\Rightarrow C=\frac{1}{2}\left[\sqrt{a+\sqrt{b}}-\sqrt{a-\sqrt{b}}\right]\)(2)
(1) cộng (2)=> dpcm

Em xin phép làm bài EZ nhất :)
4,ĐK :\(\forall x\in R\)
Đặt \(x^2+x+2=t\) (\(t\ge\dfrac{7}{4}\))
\(PT\Leftrightarrow\sqrt{t+5}+\sqrt{t}=\sqrt{3t+13}\)
\(\Leftrightarrow2t+5+2\sqrt{t\left(t+5\right)}=3t+13\)
\(\Leftrightarrow t+8=2\sqrt{t^2+5t}\)
\(\Leftrightarrow\left\{{}\begin{matrix}t\ge-8\\\left(t+8\right)^2=4t^2+20t\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}t\ge\dfrac{7}{4}\\3t^2+4t-64=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}t\ge\dfrac{7}{4}\\\left(t-4\right)\left(3t+16\right)=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}t\ge\dfrac{7}{4}\\\left[{}\begin{matrix}t=4\left(tm\right)\\t=-\dfrac{16}{3}\left(l\right)\end{matrix}\right.\end{matrix}\right.\)
\(\Rightarrow x^2+x+2=4\)\(\Leftrightarrow x^2+x-2=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-2\end{matrix}\right.\)
Vậy ....